Women, travel writing, and truth
1 online resource (vi, 193 pages)
Keywords: "The issue of truth has been one of the most constant, complex, and contentious in the cultural history of travel writing. Whether the travel was undertaken in the name of exploration, pilgrimage, science, inspiration, self-discovery, or a combination of these elements, questions of veracity and authenticity inevitably arise. Women, Travel, and Truth is a collection of twelve essays that explore the manifold ways in which travel and truth interact in women's travel writing. Essays range in date from Lady Mary Wortley Montagu in the eighteenth century to Jamaica Kincaid in the twenty-first, across such regions as India, Italy, Norway, Siberia, Austria, the Orient, the Caribbean, China and Mexico. Topics explored include blurred distinctions of fiction and non-fiction; travel writing and politics; subjectivity; displacement, and exile. Students and academics with interests in literary studies, history, geography, history of art, and modern languages will find this book an important reference"--